Assessing the efficiency of centralized use of train formations within an extensive supply network for metallurgical production - Zaruba, Oleksandr; Okorokov, Andrii; Vernyhora, Roman; Prokopa, Oleh; Khomenko, Yurii (Eastern-European Journal of Enterprise Technologies, 2025)
This study investigates a transportation-technological system that enables raw material supply by rail to meet the needs of a metallurgical enterprise. The task addressed is to assess the effectiveness of centralized use of train shipments in an extensive supply network for the needs of metallurgical production. The hypothesis of the study assumes that under conditions of centralized management of the rolling stock fleet of railroad transport within an extensive supply network, its number will be smaller than in the case of a non-centralized one. A mathematical and simulation model has been built in the AnyLogic University Researcher environment using agent and discrete-event approaches. The main criterion is the minimization of the average delivery time; additional criteria are the optimal use of the working fleet of railroad cars and train locomotives. Applying them in combination makes it possible to optimize the working fleet of railroad cars and locomotives, taking into account the extensiveness of the supply network and the conditions of centralized management. It was experimentally established that with centralized fleet management, fluctuations and volumes of metallurgical raw material residues at the enterprise depend on the loading rate of railroad cars of the sending or group of railroad cars of the stepped routes. According to the calculated values of the determination coefficients, the approximation by the exponential function turned out to be denser. The variability of raw material residues decreases with a change in the technical loading rate of the train or railroad car batch. It was established that the difference between the standard deviation for the train loading rate of 4000 t (σ(х) = 4524.7 t) and the standard deviation of 2606.5 t (σ(х) = 4524.7 t) is 1918.2 t. This corresponds to 42% of the initial value of the indicator. The proposed approach allows for a more accurate assessment of the need for a working fleet of railroad cars and locomotives, as well as improves the efficiency of transportation management